2021
DOI: 10.3390/nano11123229
|View full text |Cite
|
Sign up to set email alerts
|

Role Played by Edge-Defects in the Optical Properties of Armchair Graphene Nanoribbons

Abstract: We explore the implementation of specific optical properties of armchair graphene nanoribbons (AGNRs) through edge-defect manipulation. This technique employs the tight-binding model in conjunction with the calculated absorption spectral function. Modification of the edge states gives rise to the diverse electronic structures with striking changes in the band gap and special flat bands at low energy. The optical-absorption spectra exhibit unique excitation peaks, and they strongly depend on the type and period… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…When a 2D material is subjected to an electromagnetic field carrying the electric polarization 𝐄𝐄 � with frequency 𝜔𝜔, vertical optical transitions from occupied to unoccupied states can be triggered. The absorption coefficient is computed by using the absorption function [13].…”
Section: Theoretical Methods Of Calculationmentioning
confidence: 99%
“…When a 2D material is subjected to an electromagnetic field carrying the electric polarization 𝐄𝐄 � with frequency 𝜔𝜔, vertical optical transitions from occupied to unoccupied states can be triggered. The absorption coefficient is computed by using the absorption function [13].…”
Section: Theoretical Methods Of Calculationmentioning
confidence: 99%
“…[281] Recently, Do et al explored the unusual optical properties of defective AGNRs. [282] Hieu et al reported the optical behavior of AGNRs using the multi-orbital TB approach. [283] The optical properties of graphene nanoribbons and their tunability with size, edge structure, external field, and edge functionalization motivate researchers to fabricate graphene nanoribbon-based optoelectronic devices.…”
Section: Optical Properties Of Graphene Nanoribbonsmentioning
confidence: 99%
“…AGNRs also exhibit attractive optical properties, with efficient light absorption and emission capabilities, making them suitable for optoelectronic applications such as photodetectors [ 27 ] and light-emitting diodes [ 28 ]. Furthermore, AGNRs have shown potential in topological physics [ 29 , 30 , 31 , 32 ], with the ability to host topological edge states and phenomena such as the quantum spin Hall effect. This opens up possibilities for the development of topological quantum devices and spintronics.…”
Section: Introductionmentioning
confidence: 99%